A linguistic analysis of future narratives in adolescents with Complex Regional Pain Syndrome and their pain‐free peers. (11th December 2020) - Nimbley, Emy; Caes, Line; Jones, Abigail; Fisher, Emma; Noel, Melanie; Jordan, Abbie
Abstract: Background: Complex Regional Pain Syndrome (CRPS) is a chronic pain condition that often develops after injury, with a typical onset in adolescence. The impact of chronic pain is far‐reaching, with many adolescents reporting atypical developmental trajectories compared with peers. Social Comparison Theory offers a framework for understanding how such comparisons influence well‐being, whereby a heightened sense of disparity places adolescents at risk of poor cognitive, affective and social outcomes. Using a novel linguistic analysis programme, this study aims to investigate cognitive, affective and social language used by adolescents with CRPS in comparison to their peers during a task reflecting on their futures. Methods: A story completion task was completed by adolescents with CPRS ( n = 49) and adolescents without pain ( n = 48). This task involved asking adolescents to describe their imagined future. Narratives were analysed using a novel linguistic analysis programme, focusing on the cognitive, affective and social dimensions. Results: Findings revealed significant group differences in how adolescents with CRPS described their imagined futures. Adolescents with CRPS used significantly fewer positive affect and more negative affect, anger and sadness words, and greater insight and discrepancy words. No significant groups differences were found for social words. Conclusions: Substantial differences in cognitive and affective words were found between adolescents with and without CRPS. Findings provide novel insights into current understandings of cognitive, affective and social processes in adolescents living with chronic pain, particularly with regard to adolescent developmental trajectories, and may in turn highlight potential targets in psychosocial interventions for adolescents living with chronic pain. Significance: Social comparisons are commonly undertaken by adolescents with CRPS in relation to peers, increasing risk for poor cognitive, affective and social outcomes. Findings promote the potential importance of targeting psychosocial factors in treatments for paediatric chronic pain.